2016
DOI: 10.1093/mnras/stw855
|View full text |Cite
|
Sign up to set email alerts
|

LO Peg: surface differential rotation, flares, and spot-topographic evolution

Abstract: Using the wealth of ∼24 yr multiband data, we present an in-depth study of the starspot cycles, surface differential rotations (SDR), optical flares, evolution of star-spot distributions, and coronal activities on the surface of young, single, main-sequence, ultrafast rotator (UFR) LO Peg. From the long-term V -band photometry, we derive rotational period of LO Peg to be 0.4231 ± 0.0001 d. Using the seasonal variations on the rotational period, the SDR pattern is investigated, and shows a solar-like pattern of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…LO Peg, BO Mic, AB Dor etc. ; Karmakar et al 2016;García-Alvarez et al 2008) whereas its X-ray luminosity is less than the other fast rotating (period \1 d) active dwarf binaries (see Catalogue of Chromospherically Active Binaries; Eker et al 2008). If we compare our results with evolved active stars, we found that FR Cnc is less active with respect to them.…”
Section: Discussionmentioning
confidence: 99%
“…LO Peg, BO Mic, AB Dor etc. ; Karmakar et al 2016;García-Alvarez et al 2008) whereas its X-ray luminosity is less than the other fast rotating (period \1 d) active dwarf binaries (see Catalogue of Chromospherically Active Binaries; Eker et al 2008). If we compare our results with evolved active stars, we found that FR Cnc is less active with respect to them.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler images of LO Peg provided evidence of high polar activities (Piluso et al 2008 and references therein). Several photometric, polarimetric, and X-ray studies also carried out by Dal & Tas ¸(2003), Pandey et al (2005), Csorvási (2006), Tas ¸(2011), Karmakar et al (2016), andSavanov et al (2016).…”
Section: Introductionmentioning
confidence: 94%
“…Using the Gaia Data Release 2 (DR2), Gaia Collaboration (2018) derived parallax of this star to be 3.41±0.02 mas which corresponds to a distance of 290.7 pc by Bailer-Jones et al (2018). LO Peg is an active, single, young, main-sequence, K5-8 type UFR with a rotational period of 0.4231±0.0001 day (Karmakar et al 2016). LO Peg has been extensively studied in last two decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dark spots move across the stellar disk due to the stellar rotation and thus modulate the total brightness with the rotational period of the star. In order to determine locations of spots on the stellar surface, we have performed inversion of the phased light curves into stellar images using the light curve inversion code (iPH; see Savanov & Strassmeier 2008;Karmakar et al 2016;Savanov et al 2016). The model assumes that, due to the low spatial resolution, the local intensity of the stellar surface always has a contribution from the photosphere (I P ) and from cool spots (I S ) weighted by the fraction of the surface covered by spots, i.e., the spot filling factor f by the following relation:…”
Section: Surface Imaging With Light Curve Inversion Techniquementioning
confidence: 99%